2006
DOI: 10.1016/j.psyneuen.2006.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and hypothalamic–pituitary–adrenal axis function in healthy adults

Abstract: SummaryBackground-Traits such as behavioral inhibition and neuroticism have been linked to the development of mood and anxiety disorders. Hyperactivity of the hypothalamic-pituitary-adrenal (HPA) axis, a manifestation of the stress response, is often seen in major depression and has also been demonstrated in animals and humans with inhibited temperaments. A recent study found HPA hyperactivity in adults with high levels of neuroticism. The present study investigated associations of temperament and HPA function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 68 publications
3
44
3
Order By: Relevance
“…All of these significant correlations have been replicated in the present study (see table 2 ). We further examined the association between the TCI and DEX/CRH outcomes, and found no significant relationships between these outcomes, which was not in line with the finding of Tyrka et al [35,36] . This inconsistency might have resulted from different sample characteristics between the present and the previous two studies (e.g.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…All of these significant correlations have been replicated in the present study (see table 2 ). We further examined the association between the TCI and DEX/CRH outcomes, and found no significant relationships between these outcomes, which was not in line with the finding of Tyrka et al [35,36] . This inconsistency might have resulted from different sample characteristics between the present and the previous two studies (e.g.…”
Section: Discussioncontrasting
confidence: 55%
“…The impacts of neuroticism [37,38] and novelty seeking [35,36] on HPA axis function have been well documented, although findings on the association between neuroticism and cortisol responses to the DEX/CRH test are mixed, as described earlier [37,38] . Interestingly, O'Leary et al [78] have recently reported that nonclinical students characterized by high psychopathic personality traits lacked psychosocial stress-induced cortisol increases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The connectivity between dorsal and rostral anterior cingulate cortex and anterior insula studied by fMRI without external stimuli also correlates with HA in healthy individuals [23]. Anxiety-related traits in adulthood have also been associated with serotonin transporter gene polymorphism [24] and abnormal cortisol response during stress [25]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, serotonin, which plays a role in emotion, might also be associated with the oxytocin system and influence NS [30]. The HPA axis system might also be associated with oxytocin [37] and NS [26,38,39]. Meanwhile, we also found that the association between oxytocin and NS is independent of social support, and this may imply that oxytocin may influence NS or drug-seeking behavior via a fundamental biological mechanism.…”
Section: Discussionmentioning
confidence: 77%